The Promise and the Hope of Gene Therapy - Papanikolaou, Eleni; Bosio, Andreas (Frontiers in Genome Editing, 2021)
It has been over 30 years that visionary scientists came up with the term “Gene Therapy” suggesting that for certain indications, mostly monogenetic diseases, substitution of the missing or mutated gene with the normal allele via gene addition, could provide long lasting therapeutic effect to the affected patients and consequently improve their quality of life. This notion has recently become reality for certain diseases such as hemoglobinopathies and immunodeficiencies and other monogenetic diseases. However, the therapeutic wave of gene therapies was not only applied in this context but was more broadly employed to treat cancer with the advent of CAR-T cell therapies. This review will summarize the gradual advent of gene therapies from bench to bedside with a main focus on hemopoietic stem cell gene therapy and genome editing and will provide some useful insights about the future of genetic therapies and their gradual integration in the everyday clinical practice.